(TMT–TTF)[Pb2.6/3□0.4/3I2]3: a TTF-intercalated two-dimensional hybrid lead iodide: crystal structure and properties. (3rd January 2020) - Yin, Wen-Yu; Weng, Yi-Gang; Jiang, Miao; Yu, Shuai-Kang; Zhu, Qin-Yu; Dai, Jie
Abstract : A rare tetrathiafulvalene (TTF) derivative intercalated 2-D hybrid lead iodide with a partially oxidized TTF and Pb-vacancy in PbI2 was prepared. It exhibits a narrow band gap and high conductivity. The carrier density and photoelectric properties are first evaluated for a TTF-PbI compound. Abstract : The poorly conductive organic layers in two-dimensional (2D) perovskites create quantum wells, which hinder the carrier separation and transformation. Therefore, the search for new 2D hybrid lead-halide materials with conductive organic components is crucial to high performance 2D perovskite solar cells. Tetrathiafulvalene (TTF) and its derivatives are well-known building blocks for conductive organic materials. We report here a new compound containing TMT–TTF (tetrakis(methylthio)tetrathiafulvalene) and layered PbI2, formulated as (TMT–TTF)[Pb2.6/3 □0.4/3 I2 ]3 (1 ). Crystal structural analysis shows that compound 1 is a unique TMT–TTF-intercalated 2D hybrid lead iodide with partially oxidized TMT–TTF cations and Pb-vacancy in anion. Its structural characteristics give the compound a narrow band gap and high conductivity. Furthermore, the carrier density and the photoelectric properties are first evaluated for TTF-PbI compounds and the results show that these properties of 1 are superior to those of the previously reported TTF-PbI salt, which is attractive for exploiting new lead-halide materials.